The Intensity of Energy Consumption by Electrical Household Devices in the Pisma Asri Housing Complex, Indonesia - Santosa, Irfan; Susetyo, Budi; Ponoharjo, Ponoharjo (International Journal of Energy Economics and Policy, 2019)
The basic cost of electricity, especially in Indonesian households, has increased in recent years, reaching Rp. 1,467.28 per kilo Watt hour in the present day. In this study, we will analyze the electricity consumption of households by calculating the intensity of energy consumption. The average electricity usage in the households of 22 respondents in the Pisma Asri housing complex, Indonesia, ranged from 250 to 450 kilo Watt hour, at an average monthly cost of approximately Rp 250,000–600,000. The average electricity intensity (2–5 kilo Watt hour/ m 2 ) was below 10kilo Watt hour / m 2 , within reasonable limits. Air conditioners hadthe highest electricity consumption, accounting for 31% of the average electricity usage, followed by refrigerator sand lighting bulbs, which accounted for 26% and 14% of the electricity usage, respectively. From these results, we recommend some measures with which households can reduce their energy consumption and be relieved from some of the burdensome costs imposed by electricity supply companies. Keywords: electricity rates, household electricity consumption, electricity consumption intensity. JEL Classifications: O310, O320 DOI: https://doi.org/10.32479/ijeep.7543